Skin Barrier in Normal and Allergic Horses: What Do We Know? - Rosanna Marsella (Veterinary Sciences)
Information on skin barrier in horses is limited. A study on the epidermal ultrastructure of normal and allergic horses documented disorganized amorphous intercellular lipids in the stratum corneum of allergic samples. These findings are similar to atopic canine and human skin. Currently, there is no published study comparing skin barrier function parameters between normal and allergic horses; thus, the functional implications of the ultrastructural changes are unknown. In normal horses, body location, gender, breed, and ambient conditions affect skin barrier parameters, such as Transepidermal Water Loss. Skin microbiome studies on normal horses have highlighted the importance of season and environmental conditions, since horses housed together share similar microbiomes. Skin dysbiosis and predominance of staphylococcus have been described in horses with pastern dermatitis. Transcriptomic studies of the epidermis of normal and allergic horses have found that lesional allergic skin has substantial transcriptomic differences when compared with healthy skin, namely downregulation of genes of tight junctions, keratins, and upregulation of serine proteases and IL-13. Keratinocytes harvested from horses with insect bite hypersensitivity show upregulation of IL-31 gene expression under stimulation. While more research is clearly needed, preliminary results seem to support skin barrier differences between normal and allergic horses.